A rural ecosystem of recovery: Lessons from substance users' experiences of accessing services in Western Australia's South West. (22nd March 2022) - Cuesta‐Briand, Beatriz; Taran, Michael; Coleman, Mathew
Abstract: Introduction: Substance use is a public health issue with a greater burden in rural areas. Barriers to accessing services are exacerbated for rural substance users, with confidentiality concerns, longer travel distances, workforce issues and limited availability of services. This paper presents results from a study exploring substance users' experiences of accessing services in Western Australia's South West. Methods: This qualitative study was informed by phenomenology, and drew from social determinants and socio‐ecological theories. Data were collected through 22 semi‐structured telephone interviews with current and past substance users residing in the South West. Interviews were audio‐recorded and transcripts were subjected to thematic analysis. Results: Two themes were identified: readiness to engage as a three‐way street; and building an ecosystem of recovery networks. Effective engagement with services required multi‐level readiness. Individual readiness was strongly influenced by the social environment, while service readiness required trustworthiness and responsiveness. A number of local access barriers were identified that hindered broader system readiness. Participants experienced recovery as on‐going and require an ecosystem of support with peer support at the centre and a network of healthy relationships established through meaningful connections. Discussion and Conclusions: An effective ecosystem of support for alcohol and other drugs users in the South West should include expanded access to health, community and welfare services, with an emphasis on peer‐led support programs, and strong cross‐sector collaboration to mitigate the access barriers operating at the broader community level. Lessons from our study can inform the development of rural ecosystems of support for alcohol and other drugs users.